2021
DOI: 10.1080/19768354.2021.1920459
|View full text |Cite
|
Sign up to set email alerts
|

Loss of MeCP2 causes subtle alteration in dendritic arborization of retinal ganglion cells

Abstract: Methyl-CpG-binding protein (MeCP2) is highly expressed in neurons. It plays an important role in the development of synapses and the formation of circuits in the central nervous system (CNS). Mutations in MECP2 cause neurodevelopmental disorders and mental retardation in humans. Therefore, it has become important to determine the distribution and function of MeCP2 in vivo. The retina consists of three nuclear cell layers and two layers of synapses; neurons in each layer are connected to form fine circuits nece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Interestingly, this phenotype could be rescued with a histone deacetylase 6 (HDAC6) inhibitor suggesting that microtubule instability contributes to the primary cilia deficits observed in these models [48]. Notably, while this study provides strong evidence that support a relationship between MeCP2 function and primary cilia, another study showed that of loss of Mecp2 in mouse retina cells did not affect cilia formation [74]. Taken together, these studies suggest that MeCP2 effect on primary cilia might be cell-type dependent.…”
Section: Rett Syndromementioning
confidence: 65%
“…Interestingly, this phenotype could be rescued with a histone deacetylase 6 (HDAC6) inhibitor suggesting that microtubule instability contributes to the primary cilia deficits observed in these models [48]. Notably, while this study provides strong evidence that support a relationship between MeCP2 function and primary cilia, another study showed that of loss of Mecp2 in mouse retina cells did not affect cilia formation [74]. Taken together, these studies suggest that MeCP2 effect on primary cilia might be cell-type dependent.…”
Section: Rett Syndromementioning
confidence: 65%
“…Knock-down of KAP1 (TRIM28) in human neural progenitor cells (NPCs) generally upregulates various HERV gene expressions (Brattås et al, 2017). A gene regulatory network based on HERVs may participate in the control of gene expression of protein-coding transcripts necessary for proper development of nervous systems ( Lee et al, 2019b ; 2021b ; Zhang et al, 2019a ).…”
Section: Regulatory Factors For Hervsmentioning
confidence: 99%
“…However, its expression increases during post-natal stages, where it plays a critical role for neuronal maturation and synaptic pruning ( Johnston et al, 2001 ). MeCP2 levels are high in mature neurons, where it seems to be involved in processes of activity-dependent regulation of gene expression ( Lee et al, 2014 , 2021 ).…”
Section: Introductionmentioning
confidence: 99%